2020
DOI: 10.25220/wnj.v04.s1.0003
|View full text |Cite
|
Sign up to set email alerts
|

The Overview of Food Technology to Process Soy Protein Isolate and Its Application toward Food Industry

Abstract: Soy protein isolate (SPI) is the purest form of protein from soybean with minimum protein content of 90%. Due to its high protein content, SPI is commonly used in food processing for improving the quality of food products, including infant formula. The use of SPI in infant formula is mainly designed for infant who cannot tolerate cow’s milk-based formula. This report reviews the benefit of using SPI in soy-based infant formula rather than soymilk from whole soybean itself. It will also review the technology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Soy protein isolate (SPI), as a prime source of high-quality protein in the world, has been extensively used in beverage, baking and dairy alternatives due to its high nutritional value [1] . Compared with other plant proteins, SPI is rich in essential amino acids needed by human body, especially for the amount of lysine, which is normally lacking in other cereal [2] . Previous research demonstrated the essential amino acids in SPI could prevent cancer and reduce the levels of serum cholesterol [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Soy protein isolate (SPI), as a prime source of high-quality protein in the world, has been extensively used in beverage, baking and dairy alternatives due to its high nutritional value [1] . Compared with other plant proteins, SPI is rich in essential amino acids needed by human body, especially for the amount of lysine, which is normally lacking in other cereal [2] . Previous research demonstrated the essential amino acids in SPI could prevent cancer and reduce the levels of serum cholesterol [3] .…”
Section: Introductionmentioning
confidence: 99%
“…SPI is obtained by removing oil at lower temperature (Nishinari et al., 2014; Preece et al., 2017). SPI is the purest form of protein from soybean, with a protein content of more than 90% (Astawan & Prayudani, 2020; Yang & Li, 2020). Due to the high protein content of SPI, it is often used in food processing to improve food quality (Qin et al., 2017), including vegetarian food (X. Wang et al., 2018).…”
Section: Overview Of Spimentioning
confidence: 99%
“…Penambahan isolat protein kedelai (IPK) menjadi alternatif untuk memenuhi syarat mutu dan memperbaiki karakteristik makaroni goreng. Menurut Astawan & Prayudani (2020), IPK memiliki bentuk halus dengan kandungan protein minimal 90%. IPK ini memiliki karakteristik tekstur yang kenyal, dapat meningkatkan cita rasa dan memperbaiki sifat emulsi.…”
Section: Pendahuluanunclassified